1451. Genetic Analysis of Antibiotic Resistance Profiles of Acinetobacter baumannii Using Whole Genome Sequencing. (31st December 2020) - Brigmon, Matthew; Jinadatha, Chetan; Choi, Hosoon; Kaye, Keith S; Allton, Yonhui; Kilgore, Paul E; Beaver, Ryan; Dhar, Sorabh; Chatterjee, Piyali
Abstract: Background: Acinetobacter is known to quickly develop resistance to commonly used antibiotics. Previously we performed whole genome sequencing (WGS) and whole genome multilocus sequence typing (wgMLST) analysis in clinical Acinetobacte r isolates to determine sequence types (ST) of these isolates and mapped their distribution. In this study, we sought to characterize the genetic antibiotic resistance patterns in these isolates. Methods: Sixty-two clinical Acinetobacter isolates collected in two distinct large tertiary care hospitals in Detroit were analyzed. The samples were subjected to WGS using the NextSeq instrument (Illumina). The contigs were de novo assembled using SPAdes (v3.7.1) and wgMLST analysis was performed using BioNumerics software v7.6. The genomic sequence for each isolate was uploaded in ResFinder 3.2 and known antibiotic resistance genes were analyzed. Results: The most common resistance gene found is blaADC-25 conferring resistance to beta-lactams across all STs. Sulfonamide (sul1) and macrolide resistance (mphE/msrE) among STs were also common. ST2 (52%) was predominant for both hospitals (H1 and H2). ST2 in H2 exhibited the presence of the maximum number of resistance genes including resistance to aminoglycosides, macrolides (2), tetracyclines (tetB), beta-lactams, fluoroquinolones (aac(6')-Ib-cr), sulphonamides (sul1, sul2). ST2 had a slightly different resistance profile of beta-lactams in H1 when compared to H2. ST406 and ST15 exhibited similar antibiotic profiles in both hospitals and a single isolate of ST20 from H2 is highly antibiotic resistant. Table 1. Antimicrobial Drug Resistance Profiles of all Acinetobacter Sequence Types (STs) in H1 and H2. Table 2. Antibiotic Resistance Gene Profiles of Sequence Type 2 (ST2) isolates in H1 and H2. Conclusion: This study provides us with a snapshot of antibiotic resistant genes among circulating Acinetobacter isolates prevalent in an area. All hospital isolates demonstrated resistance to beta-lactams. Multidrug resistant ST2 isolates from both hospitals demonstrate similar antibiotic resistance gene profiles suggesting a common circulating strain in the area. No colistin resistance genes were detected in any isolates. Because Acinetobacte r infections are predominantly hospital acquired, it is important to continually monitor resistance profiles to determine the trends that may better serve both the patients and infection control practices. Disclosures: Chetan Jinadatha, MD, MPH, AHRQ (Research Grant or Support)Department of Veterans Affairs (Other Financial or Material Support, Owner: Department of Veterans Affairs. Licensed to: Xenex Disinfection System, San Antonio, TX)Inventor (Other Financial or Material Support, Methods for organizing the disinfection of one or more items contaminated with biological agents)NiH/NINR (Research Grant or Support)NSF (Research Grant or Support)Xenex Healthcare Services (Research Grant or Support)